Prenatal ethanol exposure leads to persistent anxiety-like behavior during adulthood indicated by reduced horizontal and vertical exploratory behaviors - Wang, An-Li; Micov, Veronika B.; Kwarteng, Francis; Wang, Ruixiang; Hausknecht, Kathryn A.; Oubraim, Saida; Haj-Dahmane, Samir; Shen, Roh-Yu (Frontiers in Neuroscience, 2023)
Background Fetal alcohol spectrum disorders (FASD) caused by prenatal ethanol exposure (PE) consist of many cognitive/behavioral deficits. Studies have reported that PE leads to impairments of learning and memory, attention, executive function, and anxiety. Open field (OF) is a common behavioral model which offers comprehensive ethological information. Here, we analyzed multiple parameters of OF to examine anxiety behavior and habituation after PE. Material and Methods Pregnant Sprague Dawley rats were gavaged twice/day with 0 or 3 g/kg/treatment ethanol (15% w/v) during gestational day (GD) 8–20, mimicking second-trimester heavy PE in humans. The control and PE adult offspring were subjected to OF task in different ambient light levels with or without acute stress. Results Prenatal ethanol exposure did not influence the overall locomotor activities or habituation in the OF. In lower ambient light, no PE effects could be detected. In higher ambient light, female PE rats showed less activities in the center zone, indicative of increased anxiety. Males show lower activities in the center zone only after acute stress. Rats spent <2% of the time in the center zone compared to >75% of the time in the corner zone where they engaged in frequent rearing activities (vertical exploration; exploratory rearing). Prenatal ethanol exposure led to lower rearing activities in the corner in both males and females. Acute stress masks the PE effects in males but not in females. Discussion The results support that heavy PE leads to persistent anxiety-like behavior during adulthood in both sexes. This conclusion is supported by using multiple parameters of exploratory behavior in the OF, including the rearing activities in the corner to reach reliable quantification of anxiety-like behavior.